The All-on-4 Concept Using Polyetheretherketone (PEEK)—Acrylic Resin Prostheses: Follow-Up Results of the Development Group at 5 Years and the Routine Group at One Year - Miguel de Araújo Nobre; Carlos Moura Guedes; Ricardo Almeida; António Silva; Nuno Sereno (Biomedicines, 2023)
Background: It is necessary to investigate the application of polymer materials in implant dentistry. The aim of this study was to examine the outcome of full-arch polyetheretherketone (PEEK)—acrylic resin implant-supported prostheses. Methods: Seventy-six patients were rehabilitated consecutively with 100 full-arch implant-supported prostheses of PEEK–acrylic resin (a development group (DG): 37 patients with 5 years of follow-up; a routine group (RG): 39 patients with 1 year of follow-up). The primary outcome measure was prosthetic survival. Secondary outcome measures were implant survival, marginal bone loss, biological complications, prosthetic complications, veneer adhesion, plaque levels, bleeding levels, and a patient subjective evaluation (including the Oral Health Impact Profile for the RG). Results: In both groups, prosthetic (DG: 93.6%; RG: 100%) and implant survival (DG: 98.9%; RG: 99.5%) were high, and marginal bone loss was low (DG: 0.54 mm; RG: 0.28 mm). The veneer adhesion rate was 28.6% of prostheses in DG (RG = 0%). Mechanical complications occurred in 49% and 11.8% of prostheses in DG and RG, respectively. Biological complications, plaque, and bleeding levels were low in both groups. The subjective patient evaluation was excellent in both groups (8.6 < DG < 8.8; 9.3 < RG < 9.5; OHIP = 1.38). Conclusions: Within the limitations of this study, PEEK can be considered a viable prosthetic alternative.